A Brief Note 0n the Andaman Forests and the Problem of Thinnings in Regenerated Areas and Regulation of Mixtures in the Mixed Deciduous Crop - Poovaiah, P. M. (Indian Forester, 1957)
This gives a brief note on the development of natural regeneration in the Andaman Forests and how the regulation of mixtures and the thinnings in the mixed deciduous and evergreen forests are being tackled.